Рівень обслуговування як інтегральна оцінка роботи нерегульованого перехрестя - Дворко, Олексій (Посвіт, 2019)
This article describes the concept of a service level for unregulated crossings as an indicator of their integrated work in a road-street network.
Level of service as an integrated functioning evaluation of unregulated intersections
Keywords: 656.13